High perfusion pressure as a predictor of reperfusion pulmonary injury after balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension. (June 2016) - Kinutani, Hiroto; Shinke, Toshiro; Nakayama, Kazuhiko; Taniguchi, Yu; Otake, Hiromasa; Takaya, Tomofumi; Osue, Tsuyoshi; Konishi, Akihide; Emoto, Noriaki; Hirata, Ken-ichi
Abstract: Background: Clinical efficacy of balloon pulmonary angioplasty (BPA) to the patients with non-operable chronic thromboembolic pulmonary hypertension (CTEPH) for improving pulmonary hemodynamics and exercise tolerance has been reported in these several years. However, reperfusion pulmonary injury (RPI) remains to be a major complication of BPA to overcome. This study elucidated the local predictor of RPI. Methods: Twenty-eight consecutive patients with non-operable CTEPH underwent BPA for lesions in the segmental or sub-segmental vessels. Pre- and post-BPA pulmonary arterial pressures at proximal (Pp) and distal (Pd) to the stenosis were measured by a 0.014-in. pressure wire. Positive or negative RPI was evaluated by chest computed tomography in each re-perfused segment separately 4 h after BPA. Results: Pressure measurements pre- and post-BPA were obtained from 110 lesions, where Pd and pressure ratio (Pd/Pp) increased after BPA in all lesions. Among them, RPI was observed in 49 lesions (44.5%). In the RPI-positive lesions, post-BPA Pd and post-BPA Pd/Pp were higher compared with the RPI-negative lesions. Multivariate logistic analysis revealed that the post-BPA Pd was independently associated with RPI incidence. Receiver operating characteristic curve analysis demonstrated the best cut-off value of 19.5 mm Hg for post-BPA Pd to predict RPI. Conclusions: High reperfusion pressure after BPA could be a predictor of RPI. Monitoring local pressure during BPA procedure may have a potential to reduce the incidence of RPI.